2015
DOI: 10.14432/j.macvetrev.2014.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Visibly Marked and Microchipped Lost Dogs Have a Higher Chance to Find Their Owners in Belgrade

Abstract: The aim of the study was to analyse the demographic characteristics of lost and found dogs in Belgrade, Serbia. The demographic data concerning the 246 lost and 81 found dogs in the period of 5 consecutive years (January, 2009 to January 2014) was sampled and analysed from the data bases of four organizations for animal protection in Belgrade. The recovery rate of lost dogs and the chance to be reunited again with their owners was 33%. The highest recovery rate was estimated in the category of lost dogs with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 36 publications
1
8
1
Order By: Relevance
“…Initiatives for promoting microchipping of companion rabbits may help guardians to relocate stray rabbits who may have escaped and may allow for guardians to be traced by the authorities where rabbits may have been abandoned. A study of lost and found dogs passing through animal protection organizations in Belgrade, Serbia, revealed that those with microchips were significantly more likely to be reunited with their guardians than were those who were not microchipped (Vučinić Radisavljević, Hammond-Seaman, & Ilieski, 2015), with similar findings for microchipped stray dogs in the United Kingdom (Dogs Trust, 2015). However, rabbits may be less likely to be microchipped than dogs, with a recent study showing that less than a quarter of rabbit guardians, responding to an online survey, had microchipped their rabbit(s) (Oxley Previti, Alibrandi, Briefer, & Passantino, 2015).…”
Section: Discussionmentioning
confidence: 89%
“…Initiatives for promoting microchipping of companion rabbits may help guardians to relocate stray rabbits who may have escaped and may allow for guardians to be traced by the authorities where rabbits may have been abandoned. A study of lost and found dogs passing through animal protection organizations in Belgrade, Serbia, revealed that those with microchips were significantly more likely to be reunited with their guardians than were those who were not microchipped (Vučinić Radisavljević, Hammond-Seaman, & Ilieski, 2015), with similar findings for microchipped stray dogs in the United Kingdom (Dogs Trust, 2015). However, rabbits may be less likely to be microchipped than dogs, with a recent study showing that less than a quarter of rabbit guardians, responding to an online survey, had microchipped their rabbit(s) (Oxley Previti, Alibrandi, Briefer, & Passantino, 2015).…”
Section: Discussionmentioning
confidence: 89%
“…In addition to finding that more dogs had microchips in the period after the decree, and that RTO among those with a microchip has slightly increased, their reported data showed that over the entire study period, microchipped dogs had a 77% RTO rate (1,056/1,379) compared with 42% (1,295/3,076) for non-microchipped dogs. Studies with smaller sample sizes (in the hundreds) in Spain and Serbia have also found similar differences in RTO rates ( 26 , 27 ). This study builds upon these previous results by examining microchip presence across different areas of the shelter's jurisdiction.…”
Section: Introductionmentioning
confidence: 74%
“…As reported by Surbek et al (2015), animals can run away due to the owner's inattention or irresponsibility, for mating, loneliness and boredom, etc. The reason for a missing pet can also be pet theft (Vucinic et al 2015). In case of a missing pet, the owner is obliged to report it to the stray animal shelter within three days.…”
Section: Discussionmentioning
confidence: 99%
“…While a missing pet animal is very stressful for the owner, the pets that are missing are generally frightened, hungry and thirsty, physically and mentally exhausted, may be poisoned, be killed in traffic, by other animals or malevolent people. Eventually, missing pets may be accommodated in a stray animal shelter where they can be found by their owners, be adopted to a new home, or euthanised, depending on the local regulations and shelter policy (Surbek et al 2015;Vucinic et al 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation